PCPF‐M model for simulating the fate and transport of pesticides and their metabolites in rice paddy field. Issue 12 (17th August 2017) - Boulange, Julien; Malhat, Farag; Thuyet, Dang Quoc; Watanabe, Hirozumi
Abstract: BACKGROUND: The PCPF‐1 model was improved for forecasting the fate and transport of metabolites in addition to parent compounds in rice paddies. In the new PCPF‐M model, metabolites are generated from the dissipation of pesticide applied in rice paddies through hydrolysis, photolysis and biological degradations. The methodology to parameterize the model was illustrated using two scenarios for which uncertainty and sensitivity analyses were also conducted. RESULTS: In a batch degradation experiment, the hourly forecasted concentrations of fipronil and its metabolites in paddy water were very accurate. In a field‐scale experiment, the hourly forecasted concentrations of fipronil in paddy water and paddy soil were accurate while the corresponding daily forecasted concentrations of metabolites were adequate. The major contributors to the variation of the forecasted metabolite concentrations in paddy water and paddy soil were the formation fractions of the metabolites. The influence of uncertainty included in input parameters on the forecasted metabolite concentration was high during the peak concentration of metabolite in paddy water. In contrast, in paddy soil, the metabolite concentrations forecasted several days after the initial pesticide application were sensitive to the uncertainty incorporated in the input parameters. CONCLUSION: The PCPF‐M model simultaneously forecasts the concentrations of a parent pesticide and up to three metabolites. The model was validated using fipronil and two of its metabolites in paddy water and paddy soil. The model can be used in the early stage of the pesticide registration process and in risk assessment analysis for the evaluation of pesticide exposure. © 2017 Society of Chemical Industry